The use of platelet-rich plasma in osteoarthritis - the current state of knowledge - Pawlak, Anna; Jaremek, Anna; Kępa, Joanna; Kandefer, Norbert; Wyszkowski, Michał; Grabarczyk, Aleksandra; Grad, Sylwia; Gregorek, Małgorzata; Gregorek, Paweł (Journal of Education, Health and Sport, 2023)
Introduction and objective: Osteoarthritis (OA) is a chronic condition characterized by progressive damage to the joint cartilage and bone. Platelet-rich plasma (PRP) has gained increasing interest as a potential therapeutic approach for relieving symptoms and improving joint function. The aim of this article is to present the current knowledge regarding the PRP preparation method, mechanisms of action, and treatment outcomes in OA based on scientific literature and recent research. Materials and methods: A review of scientific literature available on Google Scholar, PubMed, and Via Medica journal database was conducted using relevant keywords. State of knowledge: Platelet-rich plasma is obtained from the patient's own blood using differential centrifugation method, resulting in a concentration of platelets (PLT) that is 300-700% higher compared to the baseline. PLTs release various biologically active substances, including growth factors, which stimulate tissue repair and regeneration processes. Numerous studies have shown that PRP administration in patients with osteoarthritis of the knee and hip joints leads to pain reduction and improved joint function. The therapeutic effect yields long-lasting results, lasting up to 12 months after the completion of the treatment. Conclusions: The use of platelet-rich plasma (PRP) in the treatment of osteoarthritis presents a promising alternative to conventional therapies. However, further research is needed to confirm the effectiveness of PRP on a larger sample size and assess the long-term effects of this therapy. Knowledge regarding dosage, treatment protocols, and the duration of therapy remains limited.